Microwave Breast Imaging for Cancer Detection: Progress,Challenges and Future Prospects - Alham Monir Algomly; Nagia Ali; Mohammed Abd Alraheem Mohammed (African Journal of Advanced Pure and Applied Sciences, 2025)
Breast cancer remains one of the most common and life-threatening diseases worldwide. Standard diagnostic techniques such as mammography, ultrasound, magnetic resonance imaging (MRI), computed tomography (CT), and positron emission tomography (PET) have provided important clinical benefits but are often limited by high cost, exposure to ionizing radiation, or reduced performance in dense breast tissue. Microwave breast imaging (MBI) has recently gained attention as a safe, non-ionizing, cost-effective, and patient-friendly approach. This paper reviews the latest advances in MBI, focusing on dielectric property characterization, antenna technologies, and imaging methodologies. Current barriers—including computational complexity, safety constraints, and limited clinical validation—are discussed. The review concludes with future research priorities such as algorithmic improvement, hybrid imaging frameworks, and large-scale clinical trials that may accelerate the clinical adoption of MBI.